Muscle fibre type composition and body composition in hammer throwers - Terzis, G.; Spengos, K.; Kavouras, S.; Manta, P.; Georgiadis, G. (Journal of Sports Science & Medicine, 2010)
Aim of the present study was to describe the muscle fibre type composition and body composition of well-trained hammer throwers. Six experienced hammer throwers underwent the following measurements: one repetition maximum in squat, snatch, and clean, standing broad jump, backward overhead shot throw and the hammer throw. Dual x-ray absorptiometry was used for body composition analysis. Fibre type composition and cross sectional area was determined in muscle biopsy samples of the right vastus lateralis. Eight physical education students served as a control group. One repetition maximum in squat, snatch and clean for the hammer throwers was 245 ± 21, 132 ± 13 and 165 ± 12kg, respectively. Lean body mass was higher in hammer throwers (85.9± 3. 9kg vs. 62.7 ± 5.1kg (p < 0.01). The percentage area of type II muscle fibres was 66.1 ± 4% in hammer throwers and 51 ± 8% in the control group (p < 0.05). Hammer throwers had significantly larger type IIA fibres (7703 ± 1171 vs. 5676 ± 1270µm2, p < 0.01). Hammer throwing performance correlated significantly with lean body mass (r = 0.81, p < 0.05). These data indicate that hammer throwers have larger lean body mass and larger muscular areas occupied by type II fibres, compared with relatively untrained subjects. Moreover, it seems that the enlarged muscle mass of the hammer throwers contributes significantly to the hammer throwing performance.